Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.31235/osf.io/cnxp6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Burnout, Workload, and Morale: Describing Teacher Experiences at the Conclusion of a Pandemic Year

Abstract: Teaching during the 2020-2021 school year was fraught with challenges related to the COVID-19 pandemic, and the experiences varied widely from one policy context to another in the United States. We surveyed PK-12 teachers nationally between May-June 2021 (n=302) to understand their experiences at the conclusion of the pandemic-altered school year. Teachers shared that increased technology in elementary and secondary education was likely to persist. Teachers also shared that their morale and work-life balance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The current study's findings align with previous work on teacher well-being and the role of factors such as administrative support and job satisfaction in teacher well-being (Jakubowski & Sitko-Dominik, 2021;Sokal et al, 2021;Walter & Fox, 2021). Specifically, the low teacher morale is not surprising as Marshall et al (2022b) found teachers had lower morale at the end of the 2020-2021 school year. What is concerning is that the current findings suggest the low morale has continued through another school year.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The current study's findings align with previous work on teacher well-being and the role of factors such as administrative support and job satisfaction in teacher well-being (Jakubowski & Sitko-Dominik, 2021;Sokal et al, 2021;Walter & Fox, 2021). Specifically, the low teacher morale is not surprising as Marshall et al (2022b) found teachers had lower morale at the end of the 2020-2021 school year. What is concerning is that the current findings suggest the low morale has continued through another school year.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this exploratory study suggest that teachers had low levels of teacher morale and mental health at the conclusion of the 2021-2022 school year. A similar survey was conducted at the conclusion of the 2020-2021 school year (Marshall et al, 2022b). In that study, the researchers similarly operationalized teacher morale (Senechal et al, 2016), and found that 29.5% of teachers reported low levels of morale, compared to 53.6% in May 2022 -an 82% increase over the span of a single year.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, schools should be cognizant of the amount of work they ask of teachers, as teachers reported increased workloads throughout the COVID-19 pandemic (Love & Marshall, 2022;Marshall et al, 2022e;Walter & Fox, 2021). School leaders must provide flexibility and set realistic expectations for teachers, understanding that students are behind and trusting teachers to make sound decisions to support student learning (Chan et al, 2021;Walter & Fox, 2021).…”
Section: Discussionmentioning
confidence: 99%